Generative learning activities for online multimedia learning: when summarizing is effective but drawing is not - Lawson, Alyssa P.; Mayer, Richard E. (Frontiers in Psychology, 2024)
The goal of this study is to determine whether two commonly used generative learning activities for text-based lessons-writing a summary or creating a drawing-help students learn from a multimedia lesson involving animations with short text captions without prior training in the generative activities. Students viewed a series of four annotated animations on greenhouse gases.During pauses between the animations, students were asked to generate a written summary, to create a drawing, or to do both, whereas a control group viewed the lesson without pauses and without any generative learning activities. Students were tested immediately (Experiment 1) or after a one-week delay (Experiment 2). In both experiments, students who produced written summaries scored significantly higher on the posttest than those who engaged in no generative learning activities (d = .48 in Experiment 1, d = .54 in Experiment 2), but there was no significant difference on the posttest for students who generated drawings compared to those who engaged in no generative learning activities. In addition, those who engaged in drawing and summarizing did not have significantly different posttest performance than those engaged in summarizing alone. We conclude that writing summaries during a highly visual animated lesson is effective for learning, possibly because it encourages students to engage in generative processing during learning more than drawing and we discuss potential reasons for this in the discussion. This work helps extend generative learning theory by pinpointing potential boundary conditions for learning by drawing and learning by summarizing.